2015
DOI: 10.1210/jc.2014-3441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Parathyroidectomy Versus Observation on the Development of Vertebral Fractures in Mild Primary Hyperparathyroidism

Abstract: Even though new vertebral fractures occurred only in the observation group, the frequency was not significantly different from the surgery group. Longer follow-up is needed before firm conclusions can be drawn about the long-term safety of observation, as opposed to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
109
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(119 citation statements)
references
References 41 publications
6
109
1
3
Order By: Relevance
“…Bone remodeling is coupled in as well active acromegaly as following treatment (11), in contrast to for instance endogenous Cushing's syndrome, where bone resorption and formation are uncoupled in the active state, becoming coupled following treatment and remission (36). It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Bone remodeling is coupled in as well active acromegaly as following treatment (11), in contrast to for instance endogenous Cushing's syndrome, where bone resorption and formation are uncoupled in the active state, becoming coupled following treatment and remission (36). It is therefore to be expected that disease control in acromegaly will be followed by a decrease in bone turnover and a filling of the remodeling space followed by a relative increase in BMD (11,27), as seen in other endocrine disorders with coupled bone remodeling, following treatment (37,38). The decrease in TBS following treatment in this study, despite the increase in BMD, reflects that the two measures describe different properties of bone, especially in other conditions than postmenopausal osteoporosis (4), but are in alignment with the observed high incidence and prevalence of vertebral fractures seen in acromegaly (5,31,32,33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Five prospective studies, four of which were randomized control trials and one long-term observational study, evaluated the effect of PTx on the skeletal and renal manifestations of PHPT [59]. PTx is associated with significant improvements in bone mineral density (BMD).…”
Section: What Is the Natural History Of Phpt With Or Without Parathyrmentioning
confidence: 99%
“…Without surgical intervention, BMD is stable or decreases with long-term follow-up [58]. Data from a 5-year randomized controlled study demonstrated a lower rate of vertebral fracture post-PTx (0 vs 5 fractures) in comparison to no surgery [9]. The difference in the frequency of the fractures between observation and PTx was not statistically significant ( p  = 0.058); however, it is suggestive of skeletal protection with PTx.…”
Section: What Is the Natural History Of Phpt With Or Without Parathyrmentioning
confidence: 99%
“…Serum creatinine significantly decreased (P < 0.01) over 5 years in patients with asymptomatic PHPT followed without surgery [61]. Renal stone can be present in up to 11.4 % of patients with asymptomatic PHPT [62] and the risk of renal colic requiring hospital admission remains increased for at least 10 year after surgical cure of PHPT [63].…”
Section: A What Do We Know About the Natural History Of Mild Phpt?mentioning
confidence: 94%
“…However, though long-term randomized trial data are not available, observational studies report that more than one-third of patients develop new guidelines for surgery if observed for up to 15 year [60]. Very recently, a an extension up to 5 years of one of these prospective RCTs in patients with asymptomatic PHPT has shown that even though new vertebral fractures occurred only in the observation group, the frequency was not significantly different from that in patients who had been cured by surgery [61].…”
Section: A What Do We Know About the Natural History Of Mild Phpt?mentioning
confidence: 99%